Analysis of Breakfast Nutrients and Student Study Concentration - Mawarni, Elita Endah; Yuli Fitria; Fany Anitarini (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
One of the main targets of the Sustainable Development Goals (SDGs) program in 2030 is related to the development of Indonesian children, where Indonesian children are human resources whose welfare and intelligence must be improved. To support intelligence, concentration is needed in every learning process. The aim is to analyze the relationship between the habit of consuming nutrients in the breakfast menu with learning concentration. The method in this study is Cross-Sectional, with the population being students of the class of 2020 at a private university located in the city of Banyuwangi. Using the purposive sampling technique, the number of respondents was 115 students. Data retrieval of students' food consumption to see the level of nutritional adequacy of breakfast was obtained through data records of breakfast on the day of the test. Learning concentration was measured using the Digit Symbol Substitution Test (DSST) instrument. In addition, data on breakfast habits was obtained by filling out a questionnaire. The statistical test used in this study was the Pearson Chi-Square which was analyzed by the formula, using ρ 0,05. The study showed that most of the subjects had a regular breakfast habit (70%) and before 09.00 am (74.7%). The learning concentration of most of the subjects (64.5%) was classified as good. From the results of the Pearson Chi-Square statistical analysis, it was obtained. There is a significant relationship between the level of energy adequacy (r count = 6,594, r table = 5,991), and protein (r count = 7,874, r table = 5,991), with learning concentration. There is no significant relationship between the level of nutritional adequacy of fat and carbohydrates in the breakfast menu with learning concentration (r count < 5.991). Keywords: Breakfast Nutrients, Learning concentration, Student